Simultaneous Measurements of Geometric and Viscoelastic Properties of Hydrogel Microbeads Using Continuous‐Flow Microfluidics with Embedded Electrodes. Issue 48 (15th November 2017) - Niu, Ye; Zhang, Xu; Si, Ting; Zhang, Yuntian; Qi, Lin; Zhao, Gang; Xu, Ronald X.; He, Xiaoming; Zhao, Yi
Abstract: Geometric and mechanical characterizations of hydrogel materials at the microscale are attracting increasing attention due to their importance in tissue engineering, regenerative medicine, and drug delivery applications. Contemporary approaches for measuring the these properties of hydrogel microbeads suffer from low‐throughput, complex system configuration, and measurement inaccuracy. In this work, a continuous‐flow device is developed to measure geometric and viscoelastic properties of hydrogel microbeads by flowing the microbeads through a tapered microchannel with an array of interdigitated microelectrodes patterned underneath the channel. The viscoelastic properties are derived from the trajectories of microbeads using a quasi‐linear viscoelastic model. The measurement is independent of the applied volumetric flow rate. The results show that the geometric and viscoelastic properties of Ca‐alginate hydrogel microbeads can be determined independently and simultaneously. The bulky high‐speed optical systems are eliminated, simplifying the system configuration and making it a truly miniaturized device. A throughput of up to 394 microbeads min −1 is achieved. This study may provide a powerful tool for mechanical profiling of hydrogel microbeads to support their wide applications. Abstract : Geometric and viscoelastic properties of hydrogel microbeads are determined simultaneously using a continuous‐flow microdevice. The device can process a large number of hydrogel microbeads at low cost without optical measurements. The viscoelastic properties are derived using a quasi‐linear viscoelastic model. This work shows that viscous properties of microscale hydrogels must be accounted for in respective applications to avoid measurement errors.